Kajian terhadap Standarisasi Pendidikan Agama Kristen - Yudhi Kawangung; Nunuk Rinukti; Arnita Ernauli Marbun (JURNAL TERUNA BHAKTI, 2019)
This paper aims to examine the standardization of Christian Religious Education based on Government Regulation Number 13 of 2015 concerning Second Amendment to Government Regulation Number 19 of 2005 concerning National Education Standards, hereinafter referred to as PP No 13 of 2015 concerning National Education Standards. Christian religious education is a basic thing that must exist in Christian religious education but is not regulated in a national standard of education. The method used for the discussion of this problem is the descriptive method with a qualitative approach to the literature. The discussion and the result is that in fact Government Regulation Number 13 of 2015 concerning Second Amendment to Government Regulation Number 19 of 2005 concerning National Standards of Education in terms of Standardization of Christian Religious Education is still lacking. Christian Religious Education is not regulated in Government Regulation Number 13 of 2015 concerning Second Amendment to Government Regulation Number 19 of 2005 concerning National Education Standards but is regulated in Minister of Religion Regulation Number 27 of 2016 concerning Amendment to Ministerial Regulation Number 7 of 2012 concerning Christian Religious Education. Abstrak Makalah ini bertujuan untuk mengkaji standarisasi Pendidikan Agama Kristen berdasarkan Peraturan Pemerintah Nomor 13 Tahun 2015 tentang Perubahan Kedua Atas Peraturan Pemerintah Nomor 19 Tahun 2005 tentang Standar Nasional Pendidikan, yang selanjutnya disebut dengan PP No 13 Tahun 2015 tentang Standar Nasional Pendidikan. Pendidikan Agama Kristen merupakan hal dasar yang harus ada dalam pendidikan Keagamaan Kristen, namun tidak diatur dalam sebuah standar nasional pendidikan . Metode yang digunakan untuk pembahasan persoalan ini yakni dengan metode deskriptif dengan pedekatan kualitatif pada literatur. Pembahasan dan hasilnya yakni bahwa kenyataannya Peraturan Pemerintah Nomor 13 Tahun 2015 tentang Perubahan Kedua Atas Peraturan Pemerintah Nomor 19 Tahun 2005 tentang Standar Nasional Pendidikan dalam hal Standarisasi Pendidikan Agama Kristen masih ada kekurangan. Pendidikan Agama Kristen tidak diatur dalam Peraturan Pemerintah Nomor 13 Tahun 2015 tentang Perubahan Kedua Atas Peraturan Pemerintah Nomor 19 Tahun 2005 tentang Standar Nasional Pendidikan, melainkan diatur dalam Peraturan Menteri Agama Nomor 27 Tahun 2016 tentang Perubahan Atas Peraturan Menteri Nomor 7 Tahun 2012 tentang Pendidikan Keagamaan Kristen.